2022
DOI: 10.29407/nusamba.v7i2.17917
|View full text |Cite
|
Sign up to set email alerts
|

Competitive Advantage And Sustainable Tourism Balkondes At Borobudur Area Magelang Regency

Abstract: The phenomena of stagnant tourists’ visits at Balkondes is the background why this study is carried out will lead to the shortage of people’s revenue. It is proposed to identify the competitiveness of Balkondes tourism in Borobudur Area, Magelang Regency with the approach of Porter’s Diamond and to formulate the sustainable tourism strategy with SWOT. Data collection employs structured interview with technique of informant determination by using the combination of quota sampling technique and accidental sampli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…The results of this study support previous research that found the same results indicating that competitive advantage influences smart sustainable tourism [104]. However, in improving competitiveness and smart sustainability, it is better to focus on improving existing weaknesses, such as the division of the main tasks and functions of managers, increasing the quantity and quality of training for managers, and improving infrastructure, especially related to transportation.…”
Section: Hypothesis Testingsupporting
confidence: 87%
See 1 more Smart Citation
“…The results of this study support previous research that found the same results indicating that competitive advantage influences smart sustainable tourism [104]. However, in improving competitiveness and smart sustainability, it is better to focus on improving existing weaknesses, such as the division of the main tasks and functions of managers, increasing the quantity and quality of training for managers, and improving infrastructure, especially related to transportation.…”
Section: Hypothesis Testingsupporting
confidence: 87%
“…The literature has shown elements related to smart sustainable tourism villages, including, among others, those from the Global Sustainable Tourism Council (2013), that measure how sustainable tourism is carried out by collaborating several dimensions, including sustainable management practices, maximizing social and economic benefits, maximizing cultural benefits, and maximizing environmental benefits [103]. The dimensions and indicators added and adjusted in the smart sustainable tourism village variable are indicators of waste management following circular economy principles, namely, regenerative and restorative [104]. Then, the dimensions of smart tourism are taken from the Ambience Intelligence Tourism approach [105] and used by hotel managers and destination managers, such as those in tourist villages.…”
Section: Discussionmentioning
confidence: 99%
“…Aggregation of indicators was done by combining indicators, their sub-indicators, and their components. It can be seen in the following illustration [21]: Similar studies that discuss the preparation of CHSE indicators include [22], [23], [24], [25], [26].…”
mentioning
confidence: 99%